Dermatoglyphic Patterns and Periodontal Diseases - Chatterjee, Gargi; Manohar, Balaji; Shetty, Neema; Mathur, Aditi; Makhijani, Barkha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Background: Periodontal disease is initiated by bacterial accumulation but some risk factors like genetics also can be responsible for disease progression. Genetic determinants that exist could be suggestive of specific dermatoglyphic patterns for periodontitis. Hence, the present study was an attempt to find if there is any correlation between fingerprint patterns and periodontal diseases. Aim: To compare the fingerprint patterns in generalised chronic periodontitis and chronic generalised gingivitis subjects. Materials and methods: 800 subjects were included in the study. 437 subjects were diagnosed with generalised chronic periodontitis and 363 subjects were diagnosed with chronic generalised gingivitis. Fingerprint patterns were recorded and were analysed manually with illuminated 6X high powered magnifying glass. SPSS software was used for statistical analysis. Results: An increased frequency of radial loop pattern (39.01%) was found in chronic generalised gingivitis subjects, whereas; in generalised chronic periodontitis subjects higher frequency of ulnar loop (37.53%) and central pocket whorl pattern (36.16%) was observed. Conclusion: Dermatoglyphics could be used together with the other diagnostic aids for prediction of periodontal diseases.